2021
DOI: 10.1021/acsearthspacechem.1c00059
|View full text |Cite
|
Sign up to set email alerts
|

Probing Matrix Effects on the Heterogeneous Photochemistry of Neonicotinoid Pesticides, Dinotefuran and Nitenpyram

Abstract: The environmental fate of neonicotinoids (NNs) is a key regulatory issue due to their widespread distribution, mobility, and role in honeybee colony collapse disorder. Here, we explore the potential matrix effects of the commercial formulations on the photochemistry of two NNs, dinotefuran (DNF) and nitenpyram (NPM). The commercial formulations and the pure reagents, both embedded in KBr pellets, were irradiated at wavelengths from 254 to 350 nm. Loss of the NN and product formation were followed using Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The major solid phase photolysis products are the desnitro and urea derivatives, which form from cleavage of the N–N bond in the CN–NO 2 chromophore, resulting in a CNH (desnitro) or CO (urea) group respectively. 42,45…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major solid phase photolysis products are the desnitro and urea derivatives, which form from cleavage of the N–N bond in the CN–NO 2 chromophore, resulting in a CNH (desnitro) or CO (urea) group respectively. 42,45…”
Section: Resultsmentioning
confidence: 99%
“…An abundance of work is available on the reactions and fate of NNs in aqueous systems. 2–4,26,30–41 In addition, previous studies from this lab have reported the heterogeneous photolysis of solid NNs 42–45 as would be the case for example for NNs on leaf, soil, and dust surfaces, and the oxidation of the NN nitenpyram by gas phase ozone. 46 However, little is known about the heterogeneous reactions of solid NNs with the hydroxyl (OH) radical, which is a major atmospheric oxidant that is ubiquitous in air.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation